A Distinctly American Opportunity: Exploring Non-Standardized English(es) in Literacy Policy and Practice. (October 2016) - Smith, Patriann
National policies on language and literacy curricula reinforce standardized language approaches. These not only fail to meet the needs of non-standardized English speakers but also place our monolingual speakers at risk. When national policy does not address language in helpful, effective ways, the United States compromises citizens' literacies for effective communication, and the country becomes less competitive globally. Non-standardized English speakers' needs have not been met in literacy instruction, due to privileging only Standardized American English. This approach not only places linguistically diverse speakers as deficient and in need of fixing but also positions their monolingual counterparts (who lack this diversity) as necessarily privileged and proficient. As a way forward, national policy should move from an approach to multilingualism that is dichotomous, based only on standardized monolingual language norms, and instead adopt a translingual language approach that bridges gaps between the monolingual and the multilingual population.